Handbook of surveillance technologies - Petersen, Julie K.; Petersen, Julie K. (Boca Raton, Fla. : CRC Press, 2012)
"PREFACE This book sets the groundwork for understanding surveillance technologies by describing contemporary devices and current legislation in their historical context. The stepping stones that led to where we are today will make it easier to understand the basic 'ingredients' of today's more sophisticated devices, and will help create a mental map for understanding more specialized texts on radar, sonar, video cameras, satellite imaging, and genetic profiling. This book is suitable as a general reference and also as a foundation text for post-secondary institutions offering surveillance studies courses. Understanding Surveillance Technologies was published as the first comprehensive, introductory overview of the field of surveillance devices. The current Handbook of Surveillance Technologies comprises 18 chapters with more than 700 photos and illustrations. It is suitable for college surveillance studies in sociology and political science, professional recruiting programs, and as a reference for beginning professionals in the fields of law enforcement, forensics, and military surveillance. It is also an indispensable reference for journalists, lawmakers, and community planners. It has been designed with a flexible, modular format so the chapters can be read in almost any order and chapters that share common topics are cross-referenced to alert the reader. We are all being surveilled. It is no longer possible to avoid cameras, DNA tests, identity chips, border crossing cameras, highway monitors, ATMs, radio-chipped goods and ID cards, and other devices that record our movements, finances, and even our health"--
section 1. Introduction -- section 2. Acoustic surveillance -- section 3. Electromagnetic surveillance -- section 4. Chemical & biological surveillance -- section 5. Miscellaneous surveillance -- section 6. Index.
Rev. ed. of: Understanding surveillance technologies / J.K. Petersen. 2007.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Electronic surveillance; Electronic books